Application of a Minimally Invasive Liposuction Technique for Harvesting Fat during Transsphenoidal Surgery: A Technical Note - FUJITA, Yuichi (Neurol Med Chir (Tokyo), 2019)
Secure reconstruction in transsphenoidal surgery (TSS) is important for the prevention of the major and serious complication of postoperative cerebrospinal fluid (CSF) leak. Although abdominal fat can be safely and effectively used as a reconstruction tissue, harvesting it from the abdominal wall is traumatic and invasive, resulting in cosmetic problems. In this report, we present a method of harvesting abdominal fat using a minimally invasive liposuction technique to avoid cosmetic issues. Since 2016, we have been using fat harvested from the abdominal wall by suctioning with a dedicated syringe for reconstruction after TSS in selected cases. The liquefied fat obtained by the liposuction technique was wrapped with an oxycellulose sheet and changed its form to what we termed “fatty candy”. In this form, the fat maintained its configuration and could be handled almost as easily as a conventional fat graft. In our experienced series, there was no case with wound complication nor postoperative or late-onset CSF leak during a postoperative follow-up of at least 3 months. The fat harvested by this simple and minimally invasive liposuction technique can be expected to provide an autologous graft that is adequate not only for prevention of cosmetic problems but also for prevention of postoperative CSF leak.